Atlantic Salmon Upstream Migration Delay in a Large Hydropower Reservoir. (31st January 2021) - Babin, Amanda B.; Peake, Stephan; Linnansaari, Tommi; Curry, R. Allen; Ndong, Mouhamed; Haralampides, Katy; Jones, Ross
Abstract: Spawning success of Atlantic Salmon Salmo salar is challenged when migratory routes to natal streams are obstructed by hydropower generation stations and reservoirs that lack directional cues, potentially causing migratory delay. This study used 74 acoustic‐tagged adult Atlantic Salmon during their spawning migrations to quantify migratory success, rates, and delay through the Mactaquac Reservoir in the Saint John River, New Brunswick, during three migration seasons in 2014–2016. Tag loss or mortality was considerable, reducing the effective sample size to 34 successfully tracked adults. Of these, 41% experienced fallback over the dam, 12% were unsuccessful in exiting the reservoir, and 47% were successful in exiting the reservoir on the way to the spawning grounds. Migration rates were significantly slower in the reservoir (median ± SE = 9.3 ± 1.9 km/d) than upriver (39.0 ± 4.1 km/d), and the tagged Atlantic Salmon spent 31–53% of their time reversing direction and thus travelled longer distances (73 ± 58 km) than the minimum 37‐km midline route through the reservoir. Traveling the distance of the reservoir at the upriver migration rate could have shortened their journey by a median of 3.8 d. Sensor tags indicated that individual Atlantic Salmon experienced temperatures of 10–20°C (median ± SE = 16.0 ± 0.03°C) and migrated at depths of 5–35 m (23.4 ± 0.1 m) within the reservoir. Given that some of the energy needed for reproductive development and activities was likely appropriated by migratory delay and that a moderate proportion (47%) of adults emigrated from the reservoir, volitional passage may not be a successful management strategy in the studied reservoir. However, a substantially reduced sample size negates conclusive remarks about which management strategy would maximize survival and spawning success, and further study is needed.